2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--30462
|View full text |Cite
|
Sign up to set email alerts
|

Exam Wrappers, Reflection, and Student Performance in Engineering Mechanics

Abstract: He earned his B.Sc. (1982) in Civil Engineering and M.Sc. (1985) in Structural Engineering from Alexandria University, Egypt. He also holds a M.Sc. (1989) and a Ph.D. (1992) in Aerospace Engineering from Georgia Institute of Technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…The impact on exam performance and affective behavior columns highlight findings from the papers rather than give an exhaustive list of findings. Several studies did not find any significant impact on average exam scores when using exam wrappers [7,8,9,10,11,14]. We observe that every study that examined the grades of the lowest performing students reported meaningful improvements in performance on later exams for students who completed exam wrappers [3,14,17].…”
Section: Previous Studies and Efficacy Findingsmentioning
confidence: 60%
See 1 more Smart Citation
“…The impact on exam performance and affective behavior columns highlight findings from the papers rather than give an exhaustive list of findings. Several studies did not find any significant impact on average exam scores when using exam wrappers [7,8,9,10,11,14]. We observe that every study that examined the grades of the lowest performing students reported meaningful improvements in performance on later exams for students who completed exam wrappers [3,14,17].…”
Section: Previous Studies and Efficacy Findingsmentioning
confidence: 60%
“…Badir et al [10] report that they had observed in previous studies that students continue to repeat the same mistakes on later exams and are thus not improving their mastery of the topic. They introduce exam wrappers into their course to formalize the process of a student reviewing their performance and examining errors made with the goal of improving performance on subsequent exams.…”
Section: Previous Studies and Efficacy Findingsmentioning
confidence: 99%
“…In fact, Adaptive Follow-Up in the Mastering Engineering system was seen as punitive by some of the students rather than as a resource to encourage mastery of the material [4]. Finally, although Exam Wrappers did not seem to increase exam scores and performance; overall, having students fill out quiz and Exam Wrappers did seem to foster reflection and adjustment in most participants [5].…”
Section: Introductionmentioning
confidence: 93%
“…Within the scope of higher education, exam wrappers are popular in STEM courses as they aid students in both assessing and reflecting on their learning [4], [5], as well as refining their study strategies [6]. Additionally, a benefit of using exam wrappers is that they effectively promote metacognitive awareness [1] by prompting students to think about their behaviors and thought processes.…”
Section: Exam Wrappersmentioning
confidence: 99%
“…Through exam wrappers show considerable promise in practice, empirical evidence of wide range use of this self-evaluative tool is not abundant in the literature. Some specific collegiate courses that have documented their use of exam wrappers include engineering mechanics [4], food science and human nutrition [5], introductory science [6], as well as introductory calculus, statistics, and chemistry [1].…”
Section: Exam Wrappersmentioning
confidence: 99%